Ethical Wills – a Continental Law Perspective - Frederik Swennen; Renate Barbaix (Oñati Socio-Legal Series)
Ethical wills are testaments, or planning instruments mortis causa alike, that contain provisions regarding the deceased’s (non-economic) values rather than his (economic) valuables. The authors define and analyse the substance and form of ethical wills from a comparative Continental law perspective, drawing on Belgian, Dutch, French and German law. The focus primarily is on charges or conditions in restraint or constraint of (non-) denominational or family choices by testamentary beneficiaries; and in this context it is contended that both the doctrine of public policy (“ordre public”) and the horizontal application of the ECHR extensively restrict testamentary freedom. Nevertheless, the analogous application of estate planning techniques increasingly allows benevolent testators to plan their ethical legacy.